Splenic metastasis from gastric adenocarcinoma: A rare case. (2015) - Santos, Marco; Martins, Vilma; Moreno, Filipa; Vizcaíno, J. Ramón; Mesquita, Isabel
Highlights: We present a case of a 71-year-old patient with isolated splenic metastasis, diagnosed 6 years after primary treatment of a gastric adenocarcinoma, who underwent splenectomy. Isolated splenic metastasis, particularly from gastric adenocarcinoma, are rare. In cases of isolated splenic metastasis from gastric adenocarcinoma, fit patients should be considered for splenectomy, since there are reports of good patient survivals. Abstract: INTRODUCTION: Isolated splenic metastasis are very rare. There are only a few reported cases of patients with isolated splenic metastasis from gastric primary tumors. PRESENTATION OF CASE: We present a case of a 71-year-old patient with isolated splenic metastasis, diagnosed 6 years after primary treatment of a gastric adenocarcinoma, who previously had a lung resection also for metastasis. The patient was submitted to chemotherapy and then to splenectomy. The patient is alive and has no evidence of disease 7 months after splenectomy. DISCUSSION: We discuss the theories that explain the rare event of splenic metastasis, the route of metastization, the workup, treatment and survival of patients with isolated splenic metastasis. To the best of our knowledge, our case has the second longest interval from the primary diagnosis of gastric cancer to the diagnosis of splenic metastasis. CONCLUSION: In cases of isolated splenic metastasis from gastric adenocarcinoma, fit patients should be considered for splenectomy, since there are reports of good patient survivals.